Implementation of Pancasila On Prisoners At The Medan City Polrestabes - Burhan Sidabariba (Ipso Jure, 2024)
Pancasila is a way of life in society and nation and the implementation of the values of Pancasila is not yet optimal. It is hoped that through this writing, we will be able to understand the meaning of Pancasila values and be able to apply them to prisoners at Polrestabes better and to love their nation and state with Pancasila characteristics more. In a general context, the impact of violations of Pancasila Values can cause social, political and economic damage which ultimately affects the welfare of society. Therefore, it is important for every individual and society to maintain and commemorate Pancasila Values in everyday life. This writing research has had a positive impact on the prisoners themselves. The results of this writing research are the role of the Medan Police in implementing the application of Pancasila which is interconnected with the rule of law and restorative justice. The democratic values in Pancasila must also be implemented in prison institutions. Prisoners' participation in making decisions that affect their lives needs to be accommodated. Restorative Justice finds its footing in the basic philosophy of the fourth principle of Pancasila.